Adoptives in Xitsonga : a morphological, phonological and semantic perspective - Mamarara, Thomas Simeon (My University, 2010)
Refer to the document
Thesis (M. A. (Translation Studies and Linguistics)) -- University of Limpopo, 2010
Keywords: Tsonga language; Morphology; Morphology (Linguistics) -- Tsonga language -- South Africa; Tsonga language -- Phonology -- South Africa; Tsonga language -- Semantics -- South Africa